OPTIMUM GROWTH CONDITIONS OF ORCHID MYCORRHIZAL FUNGI FOR SIMPLE MYCORRHIZAL INOCULUM PRODUCTION - Chutima, Ruangwut; Thurian, Hathaichanoke; Roongruang, Orapin (Life Sciences and Environment Journal, 2018)
The aim of this research was to investigate the optimum growth conditions of orchid mycorrhizal fungi isolated from roots of 2 orchid species; Dendrobium lindleyi Steud. and Paphiopedilum callosum (Rchb.f.) Stein. The results revealed that the hyphal coils (peloton) of mycorrhizal fungi were found in the cortical root cells of these 2 orchid species. The totals of 9 fungal isolates were identified belonging to 3 genera including of Rhizoctonia, Xylaria and Fusarium. Then, the optimum temperature and pH of these fungal growth on Potato Dextrose Agar (PDA) were studied and the maximum fungal growth conditions were found after cultured at 30oC and adjusted pH of agar media to pH 5 (1 isolate) and pH 7 (8 isolates). For the study on effect of grain media and potting media on growth of fungal isolates, revealed that the suitable grain media for fungal growth was black bean and corn seed. While, the suitable of potting media was chopped coconut husk soaked for 12 hours with Potato Dextrose Broth (PDB). These results can be used for development of simple mycorrhizal inoculum production using suitable fungal growth conditions such as optimum temperature and pH for fungal cultivation on agar media, fungal mass production with suitable grain media and selection of suitable orchid potting materials for mycorrhizal inoculum production.